Inhibition of Catechol-O-methyltransferase Does Not Alter Effort-Related Choice Behavior in a Fixed Ratio/Concurrent Chow Task in Male Mice - DeBrosse, Adrienne C.; Wheeler, Abigail M.; Barrow, James C.; Carr, Gregory V. (Frontiers in Behavioral Neuroscience, 2020)
Effort-related choice (ERC) tasks allow animals to choose between high-value reinforcers that require high effort to obtain and low-value/low-effort reinforcers. Dopaminergic neuromodulation regulates effort-related choice behavior. The enzyme catechol-O-methyltransferase (COMT) metabolizes synaptically-released dopamine. COMT is the predominate regulator of dopamine turnover in regions of the brain with low levels of dopamine transporters, including the prefrontal cortex. Here, we evaluated the effects of the COMT inhibitor tolcapone on ERC performance in a touchscreen-based fixed-ratio/concurrent chow assay in male mice. In this task, mice were given the choice between engaging in a fixed number of instrumental responses to acquire a strawberry milk reward and consuming standard lab chow concurrently available on the chamber floor. We found no significant effects of tolcapone treatment on either strawberry milk earned or chow consumed compared to vehicle treatment. In contrast, we found that haloperidol decreased instrumental responding for strawberry milk and increased chow consumption as seen in previously published studies. These data suggest that COMT inhibition does not significantly affect effort-related decision making in a fixed-ratio/concurrent chow task in male mice.